Incidence and trends of middle ear cholesteatoma surgery and mastoidectomy in Australia—A national hospital morbidity database analysis. Issue 1 (8th December 2021) - Li, Jonathan; Jufas, Nicholas; Forer, Martin; Patel, Nirmal
Abstract: Objective: To investigate the incidence of middle ear cholesteatoma surgery and assess trends in mastoidectomy procedures in Australia. Study design: Cross‐sectional population‐based study using data from the National Hospital Morbidity Database. Methods: Admitted care episodes containing the principal diagnosis of middle ear cholesteatoma were analyzed for two 12‐month periods of 2007–2008 and 2017–2018. Surgical admissions involving mastoidectomy were identified by procedure codes. Incidence rate per 100, 000 person‐years were compared between study periods. Results: Of the 3855 middle ear cholesteatoma admissions, 3558 (92.3%) involved surgery, with the incidence rate for cholesteatoma surgical admissions estimated at 8.6 per 100, 000 (95% CI: 8.2–9.0) and 8.1 per 100, 000 (95% CI: 7.7–8.5) for 2017–2018 and 2007–2008, respectively. Population aged 10–19 years had the highest age‐specific incidence rate at 12.5 per 100, 000 (95% CI: 11.3–13.9) for 2017–2018. The 60 years and over age groups had the highest decennial percentage increase. Mastoidectomy procedures were consistently used in over half of all surgical admissions. An increase in the rate of canal wall up (CWU) mastoidectomy procedure related admissions was observed (rate ratio of 1.62 [95%CI: 1.41–1.86], P <.001) and was offset by a decreased rate of canal wall down (CWD) procedure associated admissions (0.69 [95% CI: 0.61–0.78], P <.001]). Conclusions: The incidence rate of cholesteatoma surgery in Australia is estimated at 8.6 per 100, 000. Mastoidectomy continues to play an essential role in cholesteatoma surgery with a trend favoring CWU over CWD mastoidectomy. Level of evidence: 4 Abstract : Using data from the National Hospital Morbidity Database, this cross‐sectional population‐based study examined the incidence rate of surgical admissions and the utilization of mastoidectomy procedures for the management of middle ear cholesteartoma in Australia for the two time periods of 2007–2008 and 2017–2018. From the 3855 middle ear cholesteatoma admissions analyzed, no statistically significant difference in the incidence rate of cholesteatoma surgical admissions was observed with 8.1 and 8.6 per 100, 000 person‐years for 2007–2008 and 2017–2018, respectively. While the overall incidence rate of middle ear cholesteatoma surgical admissions and incidence of admissions requiring mastoidectomy procedures has remained steady over time, cholesteatoma surgery in Australia has trended towards a more conservative approach to consist of more canal wall up (CWU) and less canal wall down (CWD) mastoidectomy procedures.